Analysis on the progress of quantum secure communication test evaluation and standardization - Junsen LAI; Bingbing WU; Rui TANG; Mengyu Ding; Wenyu ZHAO; Haiyi ZHANG (Dianxin kexue)
Quantum key distribution (QKD) based quantum secure communication (QSC) is one of the promising solutions for improving information security.With the development of experimental network construction and demonstrational application,the demand of QSC test evaluation and standardization is becoming more urgent.Based on the introduction of technology and architecture of QSC system,the latest progress of QSC test evaluation and standardization was reviewed,typical questions in test evaluation and standardization were analyzed,and development trends and prospects were also discussed.